Wittgenstein architect: un’esperienza filosofica - Damonte, Marco (Scenari, 2021)
In the studies on Wittgenstein, the house he designed and planned in Kundmanngasse for his sister Margarete between 1926 and 1928, is considered an exemplification of his thought. The aim of this paper is to reverse this approach, appreciating Wittgenstein’s experience as an architect as one of the decisive moment of his philosophical development. In order to do so, I will take the secondary literature on this theme into consideration, showing that Kundmanngasse House cannot be understood only as a representation of the philosophy of the Tractatus, nor as an anticipation of Philosophical Investigations. To value Wittgenstein as an architect I refer to his reflections contained in Culture and Value and I linger over two aspects: (1) the difference between his building and the cultural setting of that period, dominated, in architecture, by the modernism of Adolf Loos; (2) the role he has in designing the house’s interiors and finishing. I conclude the best way to approach Wittgenstein’s attempt in architecture is not to regard Kundmanngasse House as a building which represents the so called “first” or “second” Wittgenstein’s thought, but as a cultural test able to influence his conception of language (“language as use” and the notion of “following a rule”) and to support, on the one hand, the passage from the view “outside and above” language to the view “within” language and, on the other, the passage from a descriptive theory of meaning to a performative one.